A Drift Force on Submerged Body in AUV Design - Zainah, Md. Zain; Safwan, Mohd Rawi (Penerbit UMP, 2016)
During an investigation of submerged leaves and twigs sampled from tropical peat swamp forests located inPeninsular Malaysia, an anamorphic fungus not attributable to a described genus was detected and isolated in pure culture. Conidial ontogeny was thoroughly studied and illustrated using both light and SEM, which revealed a unique conidial morphology. Analysis of partial nuLSU rDNA and ITS data revealed a phylogenetic position within the Xylariales (Ascomycota), but family affiliation remained unclear.